Diksiyonaryong biswal ng arkitekturang Filipino : A visual dictionary on Filipino architecture - Fernandez, Rino D. A.; Lico, Gerardo Rey. (Espana Manila, Philippines : University of Santo Tomas Publishing House, 2015)
The book has been organized in three parts: First societies, hispanic, and american periods. The use of these historical periods is simply to guide the reader on the proper context of a particular built heritage. First societies presents the architectural terminologies of the early communities or societies, who settled in the country prior to the colonization of Spain. Hispanic period showcases the rich vocabulary of the architectural legacies of the Spanish empire during their more than 300 years of stay in the country. Lastly, American period focuses on the architectural terminologies of the american built legacy during the 50 years of rebranding the country as a democratic nation. The contemporary period was removed due to limited entries of terminologies since majority of the terminologies in this period were also part of other historical periods.
Part 1: First societies -- Apayao house ; Badjao house ; Bahay kubo ; Bontoc house ; House, early form ; Ifugao house; Ifugao rice terraces, zoning ; Ifugao rice terraces, parts ; Ivatan thatch house ; Kalinga house ; Kankanay and Ibaloi house ; Sagada house ; Samal house ; Tausug house ; Yakan house -- Part II: Hispanic period -- Church, basic parts and plan type ; Church type, cathedral ; Church type, Fortress church ; Church type, funerary chapel ; Church type, monastic ; Church type, parish ; Church type, pilgrim ; Church architectural style, earthquake baroque ; Church architectural style, Fil-hispanic Rococo ; Church architectural style, gothic revival ; Church architectural style, high renaissance ; Church architectural style, romanesque revival ; Church, altarpiece ; Church, door ; Church, vault ; Filipino house ; Filipino house, stair ; Fort ; Ivatan, stone house ; Lighthouse ; Maranao house ; Mosque ; Town plan, Plaza complex ; Town plaza, Fortress city -- Part III: American period -- American period architectural style, Italianate ; American period architectural style, Victorian ; American period architectural style, mission revival ; American period architectural style, neoclassic ; American period architectural style, neo-renaissance ; American period architectural style, neo-geothic ; American period architectural style, Art deco ; American period architectural style, Streamlined deco ; American period architectural style, Bauhaus ; Capitol building ; Gabaldon school house.
Includes bibliographical references and index.
Keywords: ARCHITECTURE -- DICTIONARIES -- PHILIPPINES